Effects of Varied Passing Drills on Passing Accuracy in Youth Academy Soccer Players - Muhammad Khairan Naufal; Ramadhan Arifin; Aryadi Rachman; Mashud (STKIP Pasundan, 2026)
This study aims to analyze the effect of varied passing drills on soccer passing accuracy among 11–14-year-old players at the Utama Raya Academy. The study employed a quasi-experimental method with a one-group pretest–posttest design. The population consisted of 150 players, while the sample comprised 20 players selected through purposive sampling based on the study criteria. Data were collected using a passing accuracy test, which involved 10 kicks at a target from a distance of 9 meters. The results showed that the average score increased from 6.10 on the pretest to 7.80 on the posttest, representing a 27.85% improvement. A paired-sample t-test yielded a significance value of 0.001 (p < 0.05), indicating a significant difference between the pre- and post-intervention results. Thus, varied passing drills were proven effective in improving soccer passing accuracy among 11–14-year-old players at the Utama Raya Academy.